Occupational Safety and Health (OSH) Education Based on Social Media in Improving Knowledge and Safety Awareness of Elementary School Students - Vania Karen Octaviani Munthe; Keleng Ate; Delita Hayanti Panjaitan; Fadila Oktaviani (JURNAL PENGMAS KESTRA (JPK), 2026)
Occupational Safety and Health (OSH) is an important aspect that should be introduced from an early age to build safe behavior and a strong safety culture in the school environment. However, the knowledge and safety awareness of elementary school students still need to be improved through educational approaches that are appropriate to their learning characteristics. This community service activity aims to enhance students’ knowledge and safety awareness through OSH education based on social media. The program was conducted with 30 elementary school students through three stages: preparation, implementation, and evaluation. The intervention was delivered using social media-based safety education combined with interactive lectures, discussions, and question-and-answer sessions. Evaluation was carried out using pre-test and post-test to measure changes in students’ knowledge and safety awareness before and after the activity. The results showed an improvement in both measured aspects. In terms of knowledge, the “good” category increased from 26.7% to 80.0%, while the “poor” category decreased from 40.0% to 3.3%. In terms of safety awareness, the “good” category increased from 30.0% to 83.3%, while the “poor” category decreased from 33.3% to 3.3%. These findings indicate that OSH education delivered through social media is effective in improving students’ understanding and safety awareness. This activity is expected to serve as a promotive and educational strategy in supporting the development of an early safety culture in elementary school environments